The Effect of Hedonic Value, and Utilitarian Value Toward Purchase Intention With Attitude as Mediation - Sulis Riptiono; Rominingtyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Purchase intention is very important in knowing the behavioral intentions of consumers who are conscious in purchasing an item, especially iphone brand smartphone products. as for some studies that have mentioned the factors that influence a person's purchase intention, namely: Brand image, hedonic value and utilitarian value, attitude. The purpose of this study was to examine the effect of hedonic value and utilitarian value, attitude towards Purchase Intention. The sampling technique in this study used purposive sampling, the sample used was 50 respondents. The analytical tool used in this research is SEM PLS. The results of this study Hedonic value affects attitude, utilitarian value affects attitude, there is a significant effect of hedonic value and utilitarian value on purchase intention. Attitude is able to mediate the influence of hedonic value utilitarian value on purchase intention.